Single-crystalline lead halide perovskite arrays for solar cells. Issue 4 (11th January 2016) - Ye, Tao; Fu, Weifei; Wu, Jiake; Yu, Zhikai; Jin, Xinyi; Chen, Hongzheng; Li, Hanying
Abstract : Single-crystalline lead halide perovskite arrays have been successfully grown on a PEDOT:PSS coated ITO substrate by the droplet-pinned crystallization method and, for the first time, single-crystalline perovskite solar cells have been demonstrated. Abstract : We have successfully grown single-crystalline lead halide perovskite arrays on a poly(3, 4-ethylene dioxythiophene):polystyrenesulfonic acid (PEDOT:PSS) coated ITO substrate by the droplet-pinned crystallization (DPC) method and, for the first time, single-crystalline perovskite solar cells have been fabricated with a power conversion efficiency of 1.73%.